A non‐flagellated, predatory soil bacterium reprograms a chemosensory system to control antifungal antibiotic production via cyclic di‐GMP signalling. (9th September 2020) - Xu, Kangwen; Shen, Danyu; Han, Sen; Chou, Shan‐Ho; Qian, Guoliang
Summary: Lysobacter enzymogenes is a non‐flagellated, soil proteobacterium that secretes a diffusible antibiotic known as heat‐stable antifungal factor (HSAF) to kill nearby fungi for food. The genome of the model strain OH11 encodes a homologous Wsp system, which is generally deployed by flagellated bacteria to achieve flagella‐dependent outputs via a c‐di‐GMP‐FleQ complex, in which c‐di‐GMP is a ubiquitous dinucleotide second messenger and FleQ is a transcription factor (TF). Here, we show that the Wsp system in the non‐flagellated OH11 participates in a unique c‐di‐GMP‐dependent signalling pathway and forms a WspR‐CdgL binary complex to alter HSAF production, in which WspR and CdgL act as a c‐di‐GMP diguanylate cyclase (DGC) and a non‐TF binding protein respectively. We found that the phosphorylation of WspR activates its DGC activity and enhances c‐di‐GMP production while inhibiting HSAF biosynthesis. The phosphorylation of WspR also plays a key role in weakening WspR‐CdgL binding and HSAF generation. Interestingly, c‐di‐GMP binding to CdgL did not seem to induce the disassociation of the WspR‐CdgL complex. These observations, along with our earlier findings, lead us to propose a model in which L . enzymogenes re‐programs the Wsp system via c‐di‐GMP signalling to regulate HSAF biosynthesis for the benefit of ecological adaptation.